Reforming China's Diplomacy - David Shambaugh (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2010)
China's diplomacy is among the many accomplishments of China during the period of reform and opening up. The People's Republic of China is emerging fully on to the world's stage, and in a largely positive fashion. It now has both interests and a presence in parts of the world completely new to China-such as Latin America and the Middle East. Beijing has managed its relations well with the major world powers-United States, Russia, and the European Union. It has transformed its regional diplomacy in Asia, reasserted a role in Africa, and has become more active in multilateral organizations. Thirty years ago, at the outset of the "reform and opening" era, China acted hesitantly on the world stage, limiting itself largely to its united front tactics against Soviet "social imperialism." Its diplomats were not very sophisticated and rarely left their embassies abroad. In the United Nations, China's preferred medium of voting was to abstain (especially on sensitive issues). In short, China's diplomacy was hesitant and not confident, inward-looking not outward looking, parochial and not sophisticated, reactive not proactive, and composed more of words than deeds. Today, these latter characterizations better describe China's diplomacy.
hdl:10398/8013
Keywords: 330; China; diplomacy; foreign relations; global corporation; reform; Diplomatie; Internationale Beziehungen; China